International counterfeiting in the European Union: a host country approach - Ribeiro, J. Cadima (2006)
This paper adopts a host country approach to empirically test the factors that attract international counterfeiting to European Union. Our empirical tests show that countries’ attractiveness to international counterfeiters is closed linked to corruption. Another finding is that economic development (measured by GDP per capita) is inversely associated with international counterfeiting. Therefore, counterfeiting must be seen as a public policy issue that affects society as a whole and that needs intervention from both nation-states and international authorities. Other key partners are brand owners, who need to have their own intellectual property protection in place and develop anti-counterfeiting tactics to prevent or reduce trademark counterfeiting. Global mutual cooperation between international companies is also important to lobby governments and politicians in general to ensure more effective enforcement of IPR (Intellectual Property Rights) laws and alert users and consumers about fakes.